Noncolloquial Arabic in Tunisian Children With Autism Spectrum Disorder: A Possible Instance of Language Acquisition in a Noninteractive Context. Issue 1 (8th August 2018) - Kissine, Mikhail; Luffin, Xavier; Aiad, Fethia; Bourourou, Rym; Deliens, Gaétane; Gaddour, Naoufel
Abstract: We have documented the significant presence of spontaneous and productive use of Modern Standard Arabic (MSA) in the speech of five Tunisian boys with autism, an unusual phenomenon. In typical development, MSA is not fully acquired before the late school years. The Arabic language in Tunisia is in a state of diglossia, and (unlike the colloquial Tunisian Arabic variety) MSA is virtually never used in everyday conversation. Television programs broadcast across the Arabic‐speaking world constitute the most important source of MSA for preschool children. Typically developing children require active social interaction to develop language, but some children with autism may use television and cartoons as noninteractional input to acquire language. This study highlighted the existence of a noninteractional language‐learning strategy that may partly compensate for the sociopragmatic deficits that characterize autism.